Wind tunnel test study on the wind load variation law of a point focus solar furnace - He, Mingfei; Huang, Penglin; Gong, Bo; Zang, Chuncheng; Wang, Zhifeng (Frontiers in Energy Research, 2023)
This work studied the wind load acting on a point focus solar furnace composed of a 110 m2 heliostat and a 77 m2 concentrator through wind tunnel testing. Based on wind tunnel test data under 305 different working conditions, the variation laws of the wind pressure coefficient, power spectral density, and wind load coefficient of the heliostat and concentrator were analyzed. The results showed that due to the interaction between the concentrator and heliostat, the wind speed near the heliostat and concentrator decreased but the turbulence intensity increased, which caused the peak wind load coefficient to rise slightly. The results suggested that a safety factor of 1.1–1.2 should be considered for structural design and optimization of solar furnaces.